Fibrotic effect of monoculture, conditioned media and coculture of fibroblast NIH3T3 cells on collagen secretion and mRNA TGF-beta expressions - Rizki Awaluddin; Dwi Aris Agung Nugrahaningsih; Prasetyastuti Prasetyastuti (Universitas Ahmad Dahlan, 2023)
Fibrosis is common profound in diabetes condition, they characterized by accumulation of extracellular matrix in tissue then cause tissue injury. The study aim to investigate effect of monoculture, conditioned media, and coculture of NIH3T3 cells in LPS-high glucose media conditions on mRNA TGF-B and collagen secretion. The fibroblast NIH3T3 were cultured with various culture type there is mono culture NIH3T3, conditioned media from RAW264.7 culture media, and coculture with RAW264.7 cells (ratio 1:1 and 1:2) in normal media (media containing 4500 mikro g/mL of glucose) and HG-LPS media (media containing LPS 0.25 mikro g/mL and D-glucose 5400 mikro g/mL). Our study shows that mRNA TGF-B and collagen secretion of fibroblast NIH3T3 cells in monoculture and conditioned media from inflammatory macrophages are not statistically different. On other hand, the TGF-B mRNA expression and the relative ratio of collagen secretion in RAW 264.7 and NIH 3T3 cell coculture media with a culture ratio of 1:1 were the highest compared to other models (p kurang dari 0.05). Our study conclude that RAW 264.7 and NIH 3T3 coculture cells (1:1) in LPS and high glucose media is appropriate for fibrosis in vitro models.